2021
DOI: 10.1186/s13102-020-00228-2
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and athletic performance according to chronotype

Abstract: Background When studying the quality of sleep in relation to athletic performance, the athlete’s chronotype and habitual time consider important factors. We aim to investigate the sleep quality and athletes’ performance according to chronotype in elite athletes. Methods Three hundred forty elite athletes (males = 261, females = 79) were recruited for the present study. All participants were screening for chronotype by the Korean versions of the Mor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…M-types go to bed and wake up early and achieve their peak mental and physical performance in the early part of the day [19], whereas E-types get up and retire later and reach their best performance during the second half of the day [16,17]. Chronotype can also influence attitudes, lifestyle, cognitive function, athletic performance, and personality traits [20][21][22][23][24][25]. M-types have been suggested to be more conscientious, agreeable, and achievement-oriented.…”
Section: Introductionmentioning
confidence: 99%
“…M-types go to bed and wake up early and achieve their peak mental and physical performance in the early part of the day [19], whereas E-types get up and retire later and reach their best performance during the second half of the day [16,17]. Chronotype can also influence attitudes, lifestyle, cognitive function, athletic performance, and personality traits [20][21][22][23][24][25]. M-types have been suggested to be more conscientious, agreeable, and achievement-oriented.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that athletic performance is influenced by chronotype, and that individuals may perform sub-optimally if forced to exercise at asynchronous times of day [ 3 , 30 ]. Furthermore, Lim et al recently demonstrated lower peak power and greater fatigue in maximal effort Wingate tests in E-types even when performance times were matched to chronotype, suggesting compromised performance in E-types [ 31 ]. These results are similar to our findings that evening-type ROTC cadets performed significantly worse on the APFT compared to I-type and M-type cadets.…”
Section: Discussionmentioning
confidence: 99%
“…Since our participants were mostly classified as morning chronotype individuals, this may explain their poorer postural balance performance in the evening. Previous studies assumed that balance performance depended on chronotype, since chronotype is known to influence attitudes, lifestyle, cognitive function, athletic performance, and personality traits (Lim et al, 2021; Makarem et al, 2020; Montaruli et al, 2021; Mulè et al, 2020; Roveda et al, 2020). Indeed, evening-type individuals reach their best performance during the second half of the day and perform worse in the morning across cognitive and physical tasks (Facer-Childs et al, 2018).…”
Section: Discussionmentioning
confidence: 99%